2003
DOI: 10.1097/01.ju.0000048974.47461.50
|View full text |Cite
|
Sign up to set email alerts
|

Penile Weight and Cell Subtype Specific Changes in a Post-Radical Prostatectomy Model of Erectile Dysfunction

Abstract: These data suggest the importance of neural integrity to maintain penile homeostasis. The loss in penile weight was consistent with the anecdotal experience of many clinicians. Decreased DNA content may have been due to significant levels of apoptosis in smooth muscle cells. Preserved protein content may suggest an increase in extracellular protein, as postulated in corporeal fibrosis. The subtunical population of apoptotic smooth muscle cells revealed a mechanism for veno-occlusive dysfunction observed after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
258
0
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(281 citation statements)
references
References 15 publications
16
258
0
7
Order By: Relevance
“…Similarly to other studies, they concluded that progressive fibrosis in the corpora cavernosa after radical prostatectomy resulted from denervation and/or an ischemic process (19). Several human and animal studies support the hypothesis of maintaining adequate penile oxygenation by preserving neurovascular bundles and thus erectile function, may play an important role in preventing irreversible penile fibrotic changes (8,14,15). User et al performed a study on postpubertal rats and grouped them according to bilateral or unilateral cavernous nerve transection versus a sham operation (14).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Similarly to other studies, they concluded that progressive fibrosis in the corpora cavernosa after radical prostatectomy resulted from denervation and/or an ischemic process (19). Several human and animal studies support the hypothesis of maintaining adequate penile oxygenation by preserving neurovascular bundles and thus erectile function, may play an important role in preventing irreversible penile fibrotic changes (8,14,15). User et al performed a study on postpubertal rats and grouped them according to bilateral or unilateral cavernous nerve transection versus a sham operation (14).…”
Section: Discussionmentioning
confidence: 77%
“…Potential pathophysiology of ED that may occur after RP has been widely discussed in several studies (13)(14)(15) and there are studies evaluating the penile length changes after RP (7,12,16). The mechanism responsible for the reduction in penile length after RP has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustained ED is more likely to be caused by secondary cavernosal trabecular smooth muscle apoptosis and its replacement with collagen. 3,4 Post-prostatectomy ED is severe and may include loss of nocturnal erections, and recovery is slower than generally reported in the literature; many men will not regain erectile function for more than 12 months. 1 ED after prostatectomy is generally treated symptomatically, as needed when intercourse is anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…Daley and coauthors 9 reported that the production of prostaglandin E1 was decreased in the cavernosal muscle, which has been previously shown to suppress the TGF-β1-induced collagen accumulation and is also oxygen dependent. Similarly, User and coauthors 10 performed bilateral neurotomy of the rat penis and found that there was a significant increase in apoptosis in the subalbugineal smooth muscle cells. This loss of smooth muscle beneath the tunica leads to venous leak and is evident clinically as venogenic ED.…”
Section: Pathophysiology Of Postprostatectomy Erectile Dysfunctionmentioning
confidence: 91%